"PREVALENCE OF Dirofilaria immitis MICROFILAREMIA IN DOMESTIC DOGS IN THE OLON COMMUNE OF SANTA ELENA PROVINCE" - Parra-Guayasamín, Sandra Gabriela; Tuarez Villón, Kleiner Agustín; Orrala Mendoza, Angela Estefanía (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2024)
Dirofilariasis is a pathology transmitted by the nematode Dirofilaria immitis, the vectors that help its transmission are Culex, Aedes, Anopheles or Mansonia mosquitoes. With this study, the prevalence of microfilariae in domestic dogs was found, through targeted sampling, blood samples were collected from 30 dogs, these were processed using the microscopic identification technique of microfilariae called “Knott's technique”, 10 were obtained. positive cases, establishing a prevalence of 33.3%. The data obtained were processed by the parametric Chi Square test, using the SPSS software, resulting in the deworming variable (internal) presenting statistically significant data, demonstrating that there is a relationship between the variable and the presence of microfilariae in the blood circulation of dogs. domestic, but rather the frequency of deworming given to the pet.
Keywords: Dirofilariasis; microfilariae; Knott's technique; diagnosis